Évaluation du Coefficient De Frottement Dans Le Cas D’un Écoulement À Surface Libre - Lahmar Karim; Jean-Pierre Larue (European Scientific Journal, ESJ, 2016)
A large number of empirical formulas such as Bazin and Manning’s formulas are used to estimate stream flows for design purpose. Discharge is calculated by standard equations that are all based on an empirical coefficient found to be a characteristic of the wall and not of its relative roughness features. This, in turn, would yield different results displayed during the calculation of Chezy coefficient while using standard materials. In open channel flows, features on the wall may have an important effect in assessing flow properties such as friction, velocity, and discharge. In this context, we have led an experimental study on a rectangular channel using the boundary layer and turbulence theory. The rectangular channel understudy is characterized by Plexiglas walls having three different roughness conditions. The study is carried out using abrasive papers with different dimensions. The results of the experiment reveals that for the three wall conditions (i.e. Plexiglas P220 and P80) and in the case of hydraulically smooth and torrential flow, the friction is estimated by Pranldt Von Karman’s formula. The same conclusion can be drawn for the different experimental tests performed on a bi-dimensional channel with a bottom made of PVC in a hydraulically smooth and fluvial flow. However, considerable discrepancy between results obtained has been inferred. Actually, there is a difference between values calculated by Chezy coefficient formula and those calculated by Manning’s formula. The latter is widely used in recent investigation especially when it comes to the transition from open channel flow to pipe flow (i.e. closed-conduit flow). In the present study, in the case of transition between a hydraulically smooth flow and a rough one (detected only in the case of P80), the friction factor is represented by a form similar to that of Colebrook White.